Perfil hemostático e hematológico de equinos com compactação de cólon maior submetidos ao tratamento medicamentoso - Daneze, Edmilson Rodrigo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The acute abdomen is reported as one of the major diseases that affect horses, constituting one of the most common emergency in equine medicine. The impactions are one of the most common forms of acute abdomen, being characterized by intestinal distention due to the stagnation of fecal mass in the intestine, and can most commonly occur in the cecum or colon. Several changes in hemostatic parameters of horses with acute abdomen are described, more common animal studies with serious diseases. In this context, the objective of this work was by serial analysis, evaluate and compare the hemostatic profile in conjunction with hematologic horses presenting large colon impactation submitted to medication treatment with healthy animals, in order to better understand the hemostatic disorders arising from the framework. For this, blood tests were performed (erythrocyte and leukocyte count) and hemostatic (platelet parameters, plasma fibrinogen, PT and APTT) in 20 adult horses, ten with medical treatment of large colon impactation (GD) and ten healthy (GC). The animals were evaluated in four stages (T0-T72), every 24 hours. In the results, it was found that the erythrocyte increased RDW in GD was associated with a possible increase in oxygen consumption during the inflammatory reaction. The leucocyte count showed changes consistent with the situation of stress and pain presented by the animals of GD on admission and with the possible inflammatory reaction triggered by injury in the microvasculature. The gradual reduction presented by fibrinogen was associated with a possible resolution of the obstruction and decreased inflammation or consumption of protein during the hemostatic process. In PT there was an increase in DG compared to GC at T0, T24 and T48. In the APTT there was considerable increase in DG T0 time. The conditions in which this study was conducted, we conclude that leukocyte changes were compatible with stress caused by obstruction ...

O abdome agudo é relatado como uma das principais enfermidades que acometem os equinos, constituindo uma das urgências mais frequentes dentro da medicina equina. As compactações são afecções mais comuns de abdome agudo, sendo caracterizadas pela distensão intestinal decorrente da estagnação do bolo fecal no intestino, podendo ocorrer mais comumente no ceco ou cólon. Diversas alterações nos parâmetros hemostáticos de equinos com abdome agudo são descritas, sendo mais comuns estudos em animais com afecções graves. Nesse contexto, o objetivo do presente trabalho foi, mediante análises seriadas, avaliar e comparar o perfil hemostático em conjunto com o hematológico, de equinos que apresentam compactação de cólon maior submetidos ao tratamento medicamentoso com animais sadios, com o intuito de melhor compreender os transtornos hemostáticos decorrentes do quadro. Para isso, foram realizados exames hematológicos (eritrograma e leucograma) e hemostáticos (plaquetograma, fibrinogênio plasmático, TP e TTPA) em 20 equinos adultos, sendo dez com compactação de cólon maior de tratamento medicamentoso (GD) e dez hígidos (GC). Os animais foram avaliados em quatro momentos (T0-T72), a cada 24 horas. Nos resultados, verificou-se que no eritrograma o aumento do RDW no GD foi associado a um possível aumento no consumo de oxigênio durante a reação inflamatória. O leucograma apresentou alterações compatíveis com a situação de estresse e dor apresentados pelos animais do GD na admissão e com a possível reação inflamatória desencadeada pelas lesões na microvasculatura. A diminuição gradativa apresentada pelo fibrinogênio foi associada a uma possível resolução da obstrução e diminuição da inflamação ou ao consumo da proteína durante o processo hemostático. No TP houve aumento no GD em comparação ao GC nos momentos T0, T24 e T48. No TTPA houve aumento considerável no momento T0 do GD. Nas condições...
Keywords: Equino; Abdome agudo; Sangue - Coagulação; Sangue - Exame; Leucócitos; Acute abdomen